Design And Evaluation of An Enterprise-Oriented Visitor Management Architecture with QR Code Authentication and RESTful Integration - Jasri Moh. Jasri; Wahyu Galih Priambodo; Bambang Bambang; Ahmad Hudawi AS; Abu Tholib; M.Fadhilur Rahman; Ahmad Ambari (Universitas Bumigora, 2026)
Visitor management plays a critical role in maintaining operational security, regulatory compliance,and administrative efficiency within organizations operating critical infrastructure. However, many existing visitor management solutions primarily focus on digital registration or QR Code-based identification without adequately supporting enterprise-level workflow integration and interoperability with existing organizational information systems. This study proposes and evaluates an enterprise-oriented visitor management architecture that integrates appointment management, QR Code authentication, RESTful interoperability, and HCL Domino communication services into a unified web-based platform. The proposed architecture was designed using Unified Modeling Language (UML), implemented with the Laravel framework, and integrated with enterprise information systems through REST APIs to support automated visitor registration, employee approval workflows, QR Code-based checkin, and email notification services. The architecture was evaluated through functional testing, user acceptance testing, and security assessment using OWASP ZAP. The evaluation results demonstrate that all functional requirements were successfully implemented, users reported positive acceptance of the system, and no critical security vulnerabilities were identified during security testing. Furthermore, the proposed architecture enables seamless interoperability between modern web technologiesand existing enterprise infrastructure while improving visitor traceability, administrative efficiency, and operational workflow management. This study contributes an enterprise-oriented reference architecture for visitor management that extends existing research beyond standalone registration systems and provides a practical implementation model for organizations requiring secure and integrated visitor management in critical industrial environments.